The Flo Adhesin Family - Ronnie G. Willaert (MDPI AG, 2021)
The first step in the infection of fungal pathogens in humans is the adhesion of the pathogen to host tissue cells or abiotic surfaces such as catheters and implants. One of the main players involved in this are the expressed cell wall adhesins. Here, we review the Flo adhesin family and their involvement in the adhesion of these yeasts during human infections. Firstly, we redefined the Flo adhesin family based on the domain architectures that are present in the Flo adhesins and their functions, and set up a new classification of Flo adhesins. Next, the structure, function, and adhesion mechanisms of the Flo adhesins whose structure has been solved are discussed in detail. Finally, we identified from Pfam database datamining yeasts that could express Flo adhesins and are encountered in human infections and their adhesin architectures. These yeasts are discussed in relation to their adhesion characteristics and involvement in infections.